2020
DOI: 10.31557/apjcp.2020.21.7.2099
|View full text |Cite
|
Sign up to set email alerts
|

Engagement of General Practice in an Australian Organised Bowel Cancer Screening Program: A Cross-Sectional Survey of Knowledge and Practice

Abstract: Background: Understanding factors causing variation in family physicians/general practitioners (GPs) screening knowledge, understanding and support of organised population-based colorectal cancer (CRC) programs can direct interventions that maximise the influence of a CRC screening recommendation from a GP. This study aims to assess contextual factors that influence knowledge and quality improvement (QI) practice directed to CRC screening in Australian general practice. Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 24 publications
(41 reference statements)
1
6
0
Order By: Relevance
“…On a care team level, we found that outdated screening knowledge influenced PHCWs level of engagement in screening, with this finding also consistent with that of previous research 16,18 . Some PHCWs outlined that they were not adopting the new self‐collection cervical screening pathway due to their incorrect belief self‐collected swabs were not as accurate as clinician‐collected swabs.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…On a care team level, we found that outdated screening knowledge influenced PHCWs level of engagement in screening, with this finding also consistent with that of previous research 16,18 . Some PHCWs outlined that they were not adopting the new self‐collection cervical screening pathway due to their incorrect belief self‐collected swabs were not as accurate as clinician‐collected swabs.…”
Section: Discussionsupporting
confidence: 87%
“…29 On a care team level, we found that outdated screening knowledge influenced PHCWs level of engagement in screening, with this finding also consistent with that of previous research. 16,18 Some PHCWs outlined that they were not adopting the new selfcollection cervical screening pathway due to their incorrect belief self-collected swabs were not as accurate as clinician-collected swabs. Although there has previously been uncertainty around the sensitivity of a selfcollected swab, this has been addressed, with an updated meta-analysis demonstrating test performance for self-collected specimens to be equally sensitive to a clinician-collected specimen.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…40 It is notable that screening for bowel cancer has been recommended for people aged 45 years and above in the USA 41 and Australia. 42 In addition, it has been recently suggested in Australia that there may be opportunities to increase CRC screening participation rates by encouraging education for primary care physicians and support for quality improvement initiatives in primary care 43 ; such approaches should also consider the implications of the age-related patterns we have found.…”
Section: Discussionmentioning
confidence: 99%